PENGARUH LINGKUNGAN BELAJAR MADRASAH TERHADAP KEMAMPUAN BERBICARA BAHASA ARAB SISWA MTs - Nurelita Surya; Hardevi Hardevi (IAI DDI Mangkoso, 2023)
This research aims to analyze the influence of the madrasah learning environment on the Arabic speaking skills (maharah al-kalam) of Madrasah Tsanawiyah (MTs) students in Jeneponto Regency. The learning environment, both physical and non-social, plays a crucial role in stimulating students' courage to communicate actively. The research method used is library research with content analysis techniques on various scientific literatures, expert books, and educational statistical data in the related region. The results of the study indicate that a conducive madrasah environment, supported by the consistent creation of bi'ah lughawiyyah (language environment), positively correlates with increased student confidence and fluency. The conclusion of the research confirms that optimizing the madrasah environment in Jeneponto requires synergy between institutional policies and teacher creativity in presenting a humanistic language atmosphere. It is recommended for madrasah managers to integrate Arabic language culture into daily activities as part of developing an excellent educational ecosystem.